Stress changes caused by exsolution of magmatic fluids within an axisymmetric inclusion - Belardinelli, Maria Elina; Nespoli, Massimo; Bonafede, Maurizio (Geophysical journal international, 2022)
SUMMARY In volcanic regions ascending magma is subject to depressurization and is generally accompanied by exsolution of volatiles. We assume a process in which these volatiles propagate upward across newly fractured and permeable rock layers, bringing a sharp increase of pore pressure and temperature within a thin disc-shaped region (inclusion). Thermo-poro-elastic (TPE) inclusion models provide a mechanism to explain seismicity and deformation induced by p and T changes in absence of new magma emplacement in volcanic contexts. They are also suitable to represent the mechanical effects due to fluid extraction and re-injection in geothermal fields. In the present work analytic solutions are provided for the displacement, strain and stress fields assuming a TPE unbounded medium. Significant deviatoric stress is generated by positive increments of pore pressure and temperature: the stress field is fully deviatoric outside the TPE inclusion, but a strong isotropic stress component is present within, leading to highly heterogeneous faulting mechanisms: if the disc plane is horizontal, thrust faulting mechanisms are favoured within the TPE disc over optimally oriented faults and normal mechanisms above. The model is easily generalized to a vertically thick disc with variable temperature and pore-pressure changes: then, an extensional environment can be obtained even within the TPE inclusion assuming upward decreasing of pore pressure and temperature changes. The supplied analytical solution may be used to model near-field TPE inclusion effects and to validate more complex numerical modelling.